Poder Judiciário Brasileiro e justiça de transição: obstáculos à responsabilização criminal de ex-agentes da ditadura militar - Dorneles, Carolina Jajah (2019)
This dissertation aims to investigate the reasons for the lack of criminal accountability of former agents of the Brazilian military dictatorship, by identifying in what way the absence or presence of familiarity with the language of international human rights law influenced the decisions of magistrates who have acted in cases involving crimes committed against political dissidents by refusing or authorizing the processing of those lawsuits. Starting from a theoretical approach based on sociological institutionalism, it was sought to test the hypothesis according to which Brazilian magistrates have little knowledge of international norms and jurisprudence, which contributed to the absence of a criminal bias in the Brazilian transitional justice system. Qualitative research methods were used with primary and secondary sources. As primary sources, it was used data obtained from semi-structured in- depth interviews with fourteen federal judges from the 1st, 2nd and 3rd regions of the Federal Regional Courts, as well as judicial decisions handed down in the thirty-eight criminal lawsuits filed by the Federal Public Prosecutor's Office in the period between 2012 and 2018. Among the secondary sources, bibliographic research was favored. The results indicated that the initial hypothesis that the lack of criminal convictions of former agents of repression is due to the lack of knowledge of magistrates about international human rights law have little explanatory potential for the non-existence of criminal convictions. Although this fact, coupled with the conservative vision of some judges who acted in these processes, and the lack of action of Non-Governmental Organizations and other actors of civil society, with the objective of sensitizing these actors to the need to perform transitional justice, may have influenced the pronouncement of unfavorable decisions, the main element that appeared in the interviews is the position adopted by the Supreme Federal Court on the issue.